Finite element analysis of finger joint / Iskanda Openg - Openg, Iskanda (1997)
This study determined the quality of the glued finger joint by evaluating its strength, durability and efficiency. In furnishing this study, tested data were taken from the work of other researcher. Since the previous study concentrated on the experimental work, therefore this study will concentrate mainly on Finite Element Analysis in generating the data. Thereon, the main objective for this study is to achieve acceptable estimate on the performance of finger joint by using the same physical laws and principles. Considering that Finite Element Analysis needs a vast and complicated computation, a computer software, namely ANSYS (Analysis System), is being used in this study. For further clarification, this report will also cover sub-topics on Finite Element Analysis Method and ANSYS Software. Hypothetically, this study will produce a similar qualitative result, compared to the one done by previous researcher. However, precise values of related quantities are expected. It is hoped that this study will help further understanding and development in this field.